2020
DOI: 10.1111/jce.14631
|View full text |Cite
|
Sign up to set email alerts
|

The utility of drug challenge testing in Brugada syndrome: A systematic review and meta‐analysis

Abstract: Introduction Brugada syndrome (BrS) is associated with ventricular arrhythmia leading to sudden cardiac death. Risk stratification is challenging, as major arrhythmic events (MAEs) are rare. We assessed the utility of drug challenge testing in BrS by a systematic review and meta‐analysis. Methods and Results We comprehensively searched the databases of MEDLINE and EMBASE from inception to May 2019. Included studies compared the incidence of MAE between spontaneous and drug challenge–induced Type 1. Mixed‐effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In the IBRYD study including 226 drug-induced type 1 BrS patients, 4.9% of them experienced a primary outcome event (appropriate ICD therapy or SCD) during a median follow-up of 106 months ( 7 ). In a recent meta-analysis including 4.099 patients with a mean follow-up of 4.5 years, the pooled annual incidence of major arrhythmic events (MAE) was 0.65% in symptomatic and 0.21% in asymptomatic drug induced type 1 BrS patients; the incidence of MAE between symptomatic drug-induced and asymptomatic spontaneous Type 1 was similar ( 8 ). The PVS failed to stratify the high-risk drug-induced BrS patients, showing a low positive predictive value (8.9% in asymptomatic; 9.6% in symptomatic); however.…”
Section: Discussionmentioning
confidence: 99%
“…In the IBRYD study including 226 drug-induced type 1 BrS patients, 4.9% of them experienced a primary outcome event (appropriate ICD therapy or SCD) during a median follow-up of 106 months ( 7 ). In a recent meta-analysis including 4.099 patients with a mean follow-up of 4.5 years, the pooled annual incidence of major arrhythmic events (MAE) was 0.65% in symptomatic and 0.21% in asymptomatic drug induced type 1 BrS patients; the incidence of MAE between symptomatic drug-induced and asymptomatic spontaneous Type 1 was similar ( 8 ). The PVS failed to stratify the high-risk drug-induced BrS patients, showing a low positive predictive value (8.9% in asymptomatic; 9.6% in symptomatic); however.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we may consider specific ethnic and geographical factors for MAE risk stratification in BrS [ 6 ]. While highest prevalence of BrS is in Southeast Asia, the prevalence in the United States reaches about 0.012%, and the prevalence in North Africa seems to be the lowest [ 6 , 7 ]. When considering diverse ethnicities, BrS is 9 times more common in Asians than in Caucasians, and 36 times more common in Asians compared to Hispanics based on population-based ECG studies [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of individuals with the Brugada ECG patterns differs largely among various regions and populations of the world [ 5 ] and is more common than BrS. Pooled worldwide prevalence of BrS is 0.5 per 1000 [ 6 ] based on ECG patterns, with highest prevalence in Southeast Asia of 3.7 per 1000, reaching up to 17.7 per 1000 in Thailand [ 6 , 7 ]. BrS is approximately nine times more common in males [ 8 , 9 ], and is one of the leading causes of SCD in males below age 40 in southeast Asia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review involving 4099 patients, Rattanawong et al . 35 found that patients with spontaneous type 1 ECG had a 2.4% annual incidence of SAEs compared with 0.65% for those with drug-induced Brugada patterns. Similarly, data from the Brugada-RISK group demonstrated that patients with a spontaneous type 1 ECG pattern had a lower mean reduced survival compared with patients without this pattern (8.8 vs. 9.8 years; P < 0.001) with a heart rate (HR) of 3.80.…”
Section: Depolarization Abnormalitiesmentioning
confidence: 95%